The prevalence and severity of injuries in field hockey drag flickers: a retrospective cross-sectional study. Issue 18 (16th September 2016) - Ng, Leo; Sherry, Dorianne; Loh, Wei Bing; Sjurseth, Andreas Myhre; Iyengar, Shrikant; Wild, Catherine; Rosalie, Simon
ABSTRACT: The drag flick is the preferred method of scoring during a penalty corner in field hockey. Performing the drag flick requires a combination of strength, coordination and timing, which may increase susceptibility to injuries. However, injury prevalence in drag flickers has not previously been investigated. Therefore, this study compared the injury prevalence and severity of lower limb and lower back injuries between drag flickers and non-drag flickers in field hockey. A total of 432 local, national and international adult field hockey players (242 males, 188 females) completed an online questionnaire to retrospectively determine the 3-month prevalence and severity of ankle, knee, hip and lower back injuries. Of this group, 140 self-identified as drag flickers and 292 as non-drag flickers. The results showed that drag flickers had significantly higher prevalence of hip (OR: 1.541; 95% CI: 1.014, 2.343) and lower back injury (OR: 1.564; 95% CI: 1.034, 2.365) compared to non-drag flickers. No significant differences were observed between drag flickers and non-drag flickers in injury prevalence at the ankle and knee. There were no significant between-group differences in injury severity scores. Overall, the prevalence of hip and lower back injuries was significantly higher in drag flickers compared to non-drag flickers.